2006
DOI: 10.1029/2005jb004124
|View full text |Cite
|
Sign up to set email alerts
|

Response of normal faults to glacial‐interglacial fluctuations of ice and water masses on Earth's surface

Abstract: [1] Changes in surface loads during glacial-interglacial cycles and the associated flexure and rebound of the lithosphere alter the stress field in actively extending regions and may lead to slip rate variations on normal faults. In particular, loading may cause a period of seismic quiescence that is followed by temporal clustering of earthquakes during and after unloading. Here we present a suite of finite element experiments to evaluate how the magnitude, distribution, and temporal evolution of the load, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 52 publications
2
54
1
Order By: Relevance
“…Johnston et al, 1998). Recent models that explicitly included a fault quantify the variations in the fault slip rate caused by glacialinterglacial changes in surface loads (Hetzel & Hampel 2005;Hampel & Hetzel 2006). As field observations show, fault slip owing to postglacial unloading can, however, not account for the total displacement on the faults as the modelled maximum scarp height in our experiments is one order of magnitude smaller than the observed maximum displacement in the field (Table 1).…”
Section: B)contrasting
confidence: 40%
“…Johnston et al, 1998). Recent models that explicitly included a fault quantify the variations in the fault slip rate caused by glacialinterglacial changes in surface loads (Hetzel & Hampel 2005;Hampel & Hetzel 2006). As field observations show, fault slip owing to postglacial unloading can, however, not account for the total displacement on the faults as the modelled maximum scarp height in our experiments is one order of magnitude smaller than the observed maximum displacement in the field (Table 1).…”
Section: B)contrasting
confidence: 40%
“…Several studies have addressed this discrepancy by adjusting either the geologic or geodetic rate with the hope of reconciling the two numbers [e.g., Bennett et al, 2004;Hetland and Hager, 2006;Oskin et al, 2007]. Other studies, however, have suggested that the difference in the geologic and geodetic estimates of fault slip rate may be revealing subtle details of the long-term faulting process [e.g., Chery and Vernant, 2006;Dolan et al, 2007;Hampel and Hetzel, 2006;Hetzel and Hampel, 2005;Luttrell et al, 2007]. If the stress perturbations from ocean loading throughout the Milankovich cycle are large enough, they may influence the seismic cycle of coastal faults sufficiently that the slip rate and recurrence interval of earthquakes on those faults would be perceptibly altered.…”
Section: Introductionmentioning
confidence: 99%
“…In a few cases, hundreds of meters of water removed as entire lakes empty affect stresses both by altering the pore pressure in the crust and inducing flexure in the lithosphere. These changes alter stress by a few megapascals over thousands of years [Hampel and Hetzel, 2006;Hetzel and Hampel, 2005] or a few hundred kilopascals over hundreds of years [Luttrell et al, 2007] and can affect the slip rate of nearby faults. On the largest and longest scale, glacial rebound following the removal of kilometers of ice may alter stresses tens of megapascals for many thousand years following unloading and can reactivate seismicity on previously dormant faults [e.g., Grollimund and Zoback, 2000;Ivins et al, 2003;Johnston et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…the ice or water volume, is represented by a pressure, which is applied to the top of the model and may vary both in space and time. Detailed information on the setup and the rheological parameters can be found in Hampel & Hetzel (2006) and Turpeinen et al (2008).…”
Section: General Model Setup and Resultsmentioning
confidence: 99%
“…On timescales of 10 4 -10 5 years, a clear link between the slip history of active faults and climate-driven mass fluctuations on Earth's surface was recently established by comparing predictions from numerical models with geological and palaeoseismological data (Hetzel & Hampel 2005;Hampel & Hetzel 2006;Hampel et al 2007Hampel et al , 2009Turpeinen et al 2008). Such mass fluctuations include variations in the volumes of ice caps, glaciers or lakes and may considerably affect the slip behaviour of faults.…”
Section: Introductionmentioning
confidence: 99%